EXPLORING THE RELATIONSHIP BETWEEN PHYSICAL LITERACY LEVELS, ENGAGEMENT AND EMOTIONALITY IN PHYSICAL EDUCATION CLASSES - Marcelo Castillo-Retamal; Andrés Concha-Salazar; Luis Castro-Morales; Javier Cerda-Aravena; Carlos Hernández-Muñoz (Journal of Physical Education)
ABSTRACT For the researchers, physical literacy (AFi) is the objective to be achieved in Physical Education, for seeking competent subjects, capable of adhering to physical activity throughout their lives, with continuous personal, social, affective, and physical development. Quantitative, descriptive-correlational research was carried out, with a non-experimental design and a non-probabilistic sample of 322 subjects, students from 12 to 18 years old from private, public, and subsidized schools in Talca, Chile. The aim was to relate the level of AFi, engagement and perceived emotionality. Data were collected by the Perceived Physical Literacy Instrument (PPLI), Behavioral Engagement Questionnaire (BEQ) and Scale for Mood Assessment (EVEA). A positive relationship was identified with a higher level of physical literacy, higher levels of happiness (r=0.37) and emotional engagement (r=0.54), decreasing the indexes of hostility (r=-0.25) and the private establishments reach the highest levels of anxiety (X̅=3.2). It is concluded that the higher the level of AFi, the greater the commitment and the greater the regulation of emotional factors.